Lactoferrin Efficiently Counteracts the Inflammation-Induced Changes of the Iron Homeostasis System in Macrophages - Cutone, Antimo; Rosa, Luigi; Lepanto, Maria Stefania; Scotti, Mellani Jinnett; Berlutti, Francesca; Bonaccorsi di Patti, Maria Carmela; Musci, Giovanni; Valenti, Piera (Frontiers in Immunology, 2017)
Human lactoferrin (hLf), an 80 kDa multifunctional iron binding cationic glycoprotein, is constitutively secreted by exocrine glands and by neutrophils during inflammation. HLf is recognized as a key element in the host immune defense system. The in vitro and in vivo experiments are carried out with bovine Lf (bLf), which shares high sequence homology and identical functions with hLf including anti-inflammatory activity. Here, in ‘pure’ M1 human macrophages, obtained by stimulation with a mixture of 10 pg/ml LPS and 20 ng/ml IFN-γ, as well as in a more heterogeneous macrophage population, challenged with high-dose of LPS (1 µg/ml), the effect of bLf on the expression of the main proteins involved in iron and inflammatory homeostasis, namely ferroportin, membrane-bound ceruloplasmin, cytosolic ferritin and transferrin receptor 1 and cytokines has been investigated. The increase of IL-6 and IL-1β cytokines, following the inflammatory treatments, is associated with both up-regulation of cytosolic ferritin and down-regulation of ferroportin, membrane-bound ceruloplasmin and transferrin receptor 1. All these changes take part into intracellular iron overload, a very unsafe condition leading in vivo to higher host susceptibility to infections as well as iron deficiency in the blood and anemia of inflammation. It is therefore of utmost importance to counteract the persistence of the inflammatory status to rebalance iron levels between tissues/secretions and blood. Moreover, levels of the anti-inflammatory cytokine IL-10 were increased in cells treated with high doses of LPS. Conversely, IL-10 decreased when the LPS/IFN-γ mix was used, suggesting that only the inflammation triggered by LPS high doses can switch on an anti-inflammatory response in our macrophagic model. Here, we demonstrate that bLf, when included in the culture medium, significantly reduced IL-6 and IL-1β production and efficiently prevented the changes of ferroportin, membrane-bound ceruloplasmin, cytosolic ferritin and transferrin receptor 1 in ‘pure’ M1 macrophages, as well as in the more heterogeneous macrophage population. In addition, the decrease of IL-10 induced by the LPS/IFN-γ mix was counteracted by bovine lactoferrin. Several drugs capable of modulating macrophagic phenotypes are emerging as attractive molecules for treating inflammation and in this sense bovine lactoferrin is no exception.